Critical illness-related corticosteroid insufficiency in dogs with systemic inflammatory response syndrome: A pilot study in 21 dogs. (July 2021) - Marchetti, M.; Pierini, A.; Favilla, G.; Marchetti, V.
Highlights: Functional corticosteroid insufficiency occurs in up to 48% in critically-ill dogs. Basal hypercortisolemia was associated with higher mortality. Low-dose hydrocortisone treatment did not have an impact on survival. Abstract: Critical illness-related corticosteroid insufficiency (CIRCI) refers to a lack of adequate corticosteroid activity, which occurs in up to 48% of dogs with sepsis. However, data regarding the occurrence of CIRCI in critically-ill dogs are still scarce. This study aimed to assess: (1) the relationship between CIRCI and clinicopathological inflammatory markers, hypotension and mortality; and (2) the impact of low-dose hydrocortisone treatment on survival. Twenty-one dogs diagnosed with systemic inflammatory response syndrome (SIRS) were enrolled in a prospective case-control study. All dogs were initially evaluated for adrenal function with an ACTH stimulation test and dogs with Δcortisol ≤ 3 μg/dL were diagnosed with CIRCI. Mean arterial pressure (MAP), white blood cell (WBC), band neutrophils (bNs), c-reactive protein (CRP), and 28-day mortality rate were assessed. Fourteen dogs were treated with low-dose hydrocortisone. The relationships between CIRCI and MAP, WBC, bN, CRP, basal cortisol and mortality were investigated, as was the association between mortality and hydrocortisone treatment. Ten of 21 (48%) dogs were diagnosed with CIRCI. Increased bNs were associated with the presence of CIRCI ( P = 0.0075). CRP was higher in dogs with CIRCI ( P = 0.02). Fourteen of 21 (66%) dogs died during the study (6/14 had CIRCI). Basal hypercortisolemia (>5 μg/dL) was associated with increased risk of mortality ( P = 0.025). Based on our diagnostic criteria, CIRCI occurs frequently in dogs with SIRS and was associated with increased bNs and increased CRP. In this study, CIRCI and low-dose hydrocortisone treatment were not significantly associated with mortality, but basal hypercortisolemia was associated with increased mortality.